Schiff's diseases of the liver - Schiff, Eugene R; Sorrell, Michael F; Maddrey, Willis C (Lippincott Williams and Wilkins, 2003)
Univ. of Miami, FL. Brandon/Hill Medical List first-purchase selection (#197). Text on the clinical and basic scientific aspects of liver disease. Additional topics include chronic viral hepatitis and alcohol-induced injury. For residents, practitioners, and students. Includes detailed halftone illustrations. Previous edition: c1999. DNLM: Liver Diseases.
Keywords: Hepatitis; hepatitida; hepatologie; Liver Diseases; nemoci jater